PEMANFATAN WEBSITE (BUSUU.COM) SEBAGAI MULTIMEDIA INTERAKTIF DALAM PEMBELAJARAN BAHASA ARAB - khoirul huda (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
The Internet is a service that makes it easy to add insight, communication, and also make it easier to find a material that is difficult to find real. Internet media is no longer merely a medium of communication, but also as an important part of the world of business, industry, education and social relations. One of the web-based internet sites that are developing at this time and interested everyone is the utilization of Multimedia in the form of website. This research uses a qualitative approach because the problem in this research is holistic, considering there are many things that need to be explored in Busuu.com website so that the researcher needs to deepen it so that this research succeed to get explanation, pattern or model of website based learning as shown by Busuu.com. This site is widely used by some people as a medium of learning language materials because it has an interactive power in studying and mastering two foreign languages ​​such as Arabic and English.